2012
DOI: 10.1039/c1nj20437h
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of (all-E)-lycopene and synthetic apo-lycopenoids in a chemical model of oxidative stress in the gastro-intestinal tract

Abstract: Lycopene, the main pigment of tomato, is known to have protective effects on health. Its metabolites could also be involved in these effects. Potentially bioactive lycopene metabolites namely apo-10 0 -lycopenol, apo-10 0 -lycopenal, apo-14 0 -lycopenol, apo-14 0 -lycopenal, and apo-11-lycopenoids with alcohol, carboxylic acid, aldehyde and ethyl ester terminal groups were obtained by organic synthesis as (all-E) stereoisomers using HWE condensation reactions. The ability of (all-E)-lycopene and the synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…1a and peak (I) in Fig. 3a] displays a UV-VIS spectrum close to that reported for apo-10′-lycopenal [8], although we could not confirm its chromatographic behaviour due to the lack of authentic standard.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…1a and peak (I) in Fig. 3a] displays a UV-VIS spectrum close to that reported for apo-10′-lycopenal [8], although we could not confirm its chromatographic behaviour due to the lack of authentic standard.…”
Section: Discussionsupporting
confidence: 63%
“…In this sense, different apo-carotenoids (i.e. β-apo-carotenals and apolycopenoids) have been reported to be formed under in vitro conditions and also to be present in foods and human tissues as a result of xanthophyll and lycopene metabolism [8,11,12]. Interestingly, under UPLC conditions, one of these "unknown" peaks [peak (II) in Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As has been observed by others (27), we found that homologation of 10 to ethyl apo-11-lycopenoate (13) by Wadsworth-Emmons reaction (Fig. 5) resulted in an approximately 3:1 isomeric mixture of the 2E/Z products.…”
Section: Apolycopenoid Synthesessupporting
confidence: 67%
“…Although xanthophylls having conjugated polyene chains with electro-withdrawing groups might be slightly less reducing than carotenes, this interpretation does not hold for the bacterial carotenoids. The polarity of carotenoids is another important factor to consider [19]. Indeed, xanthophylls in general and so glycosylated carotenoids in particular tend to be more localized at the edge of the micelles, thus being more exposed to oxidants in the aqueous phase.…”
Section: Discussionmentioning
confidence: 99%